Radar Interferometric Experimental Reconstruction of Three-Dimensional Displacement Vectors and Mode Shapes for Masonry Constructions. Issue 1 (1st April 2022) - Castellano, A; Camassa, D; Fraddosio, A; Piccioni, M D
Abstract: Radar interferometry is an innovative measurement technique capable of remotely measuring vibrations in terms of displacement history. It apparently allows overcoming some major drawbacks of the plodding and time-consuming conventional accelerometric experimental setup for vibration testing. Indeed, radar interferometry does not require any access to the structure; moreover, its use is simpler and faster. Therefore, this technique appears very appealing for ambient vibration testing on structures, and in particular on architectural heritage masonry constructions. However, radar interferometry is still affected by some relevant limitations, that currently outweigh the advantages. One of the most important limitations is that displacements are measured only along the line-of-sight; therefore, it is not possible to determine the whole three-dimensional displacement vector for moving structural points and, consequently, to reconstruct three-dimensional mode shapes of structures, whose knowledge is crucial for characterizing the dynamic behavior of structures and for detecting eventual damages. In this paper, a theoretical and experimental approach for reconstructing both three-dimensional displacement vectors and mode shapes of masonry constructions is proposed. This approach is based on the simultaneous use of two synchronized radar interferometers, and on the application of a theoretical model assuming a specific kinematical constraint, which is generally plausible in the case of masonry constructions. The proposed approach has been validated through in-situ experimental tests on a masonry bell tower.